A Decision Support System to Achieve Self-Sufficiency of Soybean (Case: Central Java Province, Indonesia) - Muhammad Hisjam; Nancy Octyajati; Wahyudi Sutopo; Ahad Ali (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2020)
Soybean self-sufficiency in Central Java Province is a problem that is difficult to realize at this time. As an important commodity, self-sufficiency becomes a serious concern for the government. Supply chain management of soybean is related to the integration of supply, demand, and distribution of soybean. The characteristics of entities involved in the soybean supply chain are complex, dynamic, and probabilistic that make the problem cannot be solved using an analytical model and it becomes too risky for trial and error. A suitable tool is using a simulation model. This paper deals with developing a Decision Support System (DSS) using a simulation model that will assist the government in adopting policies in order to achieve self-sufficiency of soybean and the improvement of farmer's welfare. DSS will help decision-makers to try various scenarios of policy in an easy way. The method was started with developing model components, then decision components, and next creating user interfaces. The simulation and system modeling is created by using Powersim software with the intent to obtain the simulation and single document interface (SDI) of the supply chain model. The result shows that land expansion policy is a top priority for realizing food self-sufficiency while increasing productivity and reducing costs of agricultural activities are the main priorities for improving the welfare of farmers.